Nickel oxide doped noble metals supported catalysts for carbon dioxide methanation and desulfurization reactions - Susilawati Toemen, 1986-; Wan Azelee Wan Abu Bakar; Rusmidah Ali; Fakulti Sains (2011)
Thesis (Sarjana Sains (Kimia)) - Universiti Teknologi Malaysia, 2011